BMSC-Derived Exosomes Alleviate Sepsis-Associated Acute Respiratory Distress Syndrome by Activating the Nrf2 Pathway to Reverse Mitochondrial Dysfunction - Zhenzhen Li; Beijie Zheng; Chenchen Liu; Xiang Zhao; Yupeng Zhao; Xiangrui Wang; Lei Hou; Zhongwei Yang (Stem Cells International)
Type II alveolar epithelial cell (AECII) apoptosis is one of the most vital causes of sepsis-induced acute respiratory distress syndrome (ARDS). Recent evidence has proved that bone mesenchymal stem cell-derived exosomes (BMSC-exos) can effectively reduce sepsis-induced ARDS. However, the function and molecular mechanism of BMSC-exos in sepsis-induced AECII apoptosis remain to be elucidated. In the present study, a more significant number of AECII apoptosis, high mitochondrial fission p-Drp1 protein levels, and low levels of mitochondrial biogenesis-related PGC1α, Tfam, and Nrf1 proteins accompanied with ATP content depression were confirmed in AECIIs in response to sepsis. Surprisingly, BMSC-exos successfully recovered mitochondrial biogenesis, including the upregulated expression of PGC1α, Tfam, Nrf1 proteins, and ATP contents, and prohibited p-Drp1-mediated mitochondrial fission by promoting Nrf2 expression. However, the aforementioned BMSC-exo reversal of mitochondrial dysfunction in AECIIs can be blocked by Nrf2 inhibitor ML385. Finally, BMSC-exos ameliorated the mortality rate, AECII apoptosis, inflammatory cytokine storm including HMGB1 and IL-6, and pathological lung damage in sepsis mice, which also could be prevented by ML385. These findings reveal a new mechanism of BMSC-exos in reversing mitochondrial dysfunction to alleviate AECII apoptosis, which may provide novel strategies for preventing and treating sepsis-induced ARDS.